Features of the structure of soil profiles within Odessa city - Khokhryakova, A. I. (AgroChemistry and Soil Science, 2020)
The results of substantiation of the need to improve methodological approaches to soil diagnostics on the territory of settlements, as well as the need to approve a single list of indices of soil genetic horizons of urban areas are presented. Soil research in the city of Odessa was performed at 43 key sites (70 soil profile cuts). Within the city, two classes of soils - natural and anthropogenic (anthropogenically transformed and anthropogenically created (urbanozem)) were identified and parameterized morphological characteristics of soils were determinated. The results of the research were used to improve the methods of diagnostics of anthropogenically transformed and anthropogenically created soils by introducing new indices of genetic horizons and auxiliary graphic symbols to indicate the physical and mechanical transformation of the soil profile. It is revealed that the processes of soil formation within the city in the steppe zone are determined by both zonal natural factors and specific anthropogenic impact within a large industrial city. Signs of soil disturbance are, first, the transformation of the structure of the profile, the change in the depth of genetic horizons, the inclusion of various artifacts, and so on. Zonal soils in urban areas (southern chernozems within the city of Odessa) due to the expansion of the complex of soil-forming processes (greater variety of soil formation factors) have wider ranges of depth of genetic horizons compared to natural soil. Urban soils also have a high variability in the depths of diagnostic horizons, which depends on the functional use of land within the city.